2017
DOI: 10.1038/emi.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Comparative epidemiology of Middle East respiratory syndrome coronavirus (MERS-CoV) in Saudi Arabia and South Korea

Abstract: MERS-CoV infection emerged in the Kingdom of Saudi Arabia (KSA) in 2012 and has spread to 26 countries. However, 80% of all cases have occurred in KSA. The largest outbreak outside KSA occurred in South Korea (SK) in 2015. In this report, we describe an epidemiological comparison of the two outbreaks. Data from 1299 cases in KSA (2012–2015) and 186 cases in SK (2015) were collected from publicly available resources, including FluTrackers, the World Health Organization (WHO) outbreak news and the Saudi MOH (MOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 31 publications
12
87
0
3
Order By: Relevance
“…It is associated with a 35% mortality rate, primarily due to multiorgan failure (Rivers et al, 2016;Zumla et al, 2015). Middle East respiratory syndrome-coronavirus (MERS-CoV) can be transmitted either from non-human to human where dromedary camels are a major reservoir host for this virus or by a human to the human transmission which requires close contact (Cotten et al, 2013;de Groot et al, 2013) Many studies suggested that MERS-CoV has a male predominance prevalence with a median age of 40 years at illness onset (Aleanizy et al, 2017;Chan et al, 2015;Chen et al, 2017). Data showed that underlying immunodeficiency or immunosuppressant medications and therapies or diabetes mellitus are strongly associated with increased morbidity and mortality (Aleanizy et al, 2017;Chen et al, 2017 summary, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with a 35% mortality rate, primarily due to multiorgan failure (Rivers et al, 2016;Zumla et al, 2015). Middle East respiratory syndrome-coronavirus (MERS-CoV) can be transmitted either from non-human to human where dromedary camels are a major reservoir host for this virus or by a human to the human transmission which requires close contact (Cotten et al, 2013;de Groot et al, 2013) Many studies suggested that MERS-CoV has a male predominance prevalence with a median age of 40 years at illness onset (Aleanizy et al, 2017;Chan et al, 2015;Chen et al, 2017). Data showed that underlying immunodeficiency or immunosuppressant medications and therapies or diabetes mellitus are strongly associated with increased morbidity and mortality (Aleanizy et al, 2017;Chen et al, 2017 summary, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, humanto-human transmission through close contact of an infected individual with family members and health care workers was also confirmed [18,19]. For example, Chen X. et al [20] reported that 94.1% of MERS-CoV cases in the 2015 outbreaks in Korea had a history of contact in hospital facilities, and six cases (3.2%) were infected with MERS-CoV through community contacts.…”
Section: Middle East Respiratory Syndrome (Mers)mentioning
confidence: 92%
“…While in Korea the transmission pattern was almost exclusively nosocomial, in KSA zoonotic transmission, human-to-human transmission and unknown pathways were all present in addition to nosocomial infection (Chen et al, 2017). In some 59.9% of cases in KSA outbreaks, exposure risk was unknown (Chen et al, 2017). Thus in addition to the infection prevention and control guidelines for healthcare facilities, WHO has also issued guidance on potential zoonotic transmission in the community, in particular with respect to dromedary camels which are recognized as a major MERS-CoV host reservoir and animal source for human infection (Middle East respiratory syndrome coronavirus (MERS-CoV).…”
Section: Infection Prevention and Control Measures In Saudi Arabiamentioning
confidence: 99%
“…However, diligence in needed in maintaining surveillance standards and furthering understanding of transmission patterns within KSA and elsewhere. Comparison of epidemiology of KSA outbreaks to that of the Republic of Korea 2015 outbreak suggests that while there are similarities in terms of mean age of infected individuals (51 and 54 y respectively) and the higher risk of infection or death for older males (≥70 y), nevertheless there is evidence that transmission patterns and risk factors are different in KSA (Chen et al, 2017). While in Korea the transmission pattern was almost exclusively nosocomial, in KSA zoonotic transmission, human-to-human transmission and unknown pathways were all present in addition to nosocomial infection (Chen et al, 2017).…”
Section: Infection Prevention and Control Measures In Saudi Arabiamentioning
confidence: 99%